2009
DOI: 10.1097/sle.0b013e3181a031f5
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Plastic Biliary Stents and Endoscopic Retrieval

Abstract: Retrieval of a proximally migrated stent requires experience with different endoscopic devices. Moreover, distal migration needs attention because it can cause severe complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 25 publications
1
48
1
3
Order By: Relevance
“…16 In hilar biliary strictures, longer stents were required to decompress dilated intrahepatic ducts. Longer stents that are usually used in proximal strictures often migrate distally, and shorter stents that are usually used in distal strictures often migrate proximally.…”
Section: Discussionmentioning
confidence: 99%
“…16 In hilar biliary strictures, longer stents were required to decompress dilated intrahepatic ducts. Longer stents that are usually used in proximal strictures often migrate distally, and shorter stents that are usually used in distal strictures often migrate proximally.…”
Section: Discussionmentioning
confidence: 99%
“…One option is to attempt endoscopic retrieval. A recent review showed that this might be difficult for proximally migrated stents (71.4% success) but was more successful for distally migrated stents (100% successfully retrieved) [4]. Indeed 80-86% success for proximal stent retrieval has also been reported but it is a technical challenge to the endoscopist [5].…”
Section: Discussionmentioning
confidence: 99%
“…Proximally migrated biliary stents should be retrieved as they can cause cholangitis or jaundice if left in situ [56]. If possible, the endoscopist can attempt to directly grab the migrated stent and gently pull it out using biopsy forceps under endoscopic or fluoroscopic guidance [56,57]. If forceps are ineffective, we recommend approaching the stent much like a common bile duct stone.…”
Section: Stent Migrationmentioning
confidence: 99%
“…A guidewire should be advanced through the lumen of the stent (if 10 F or greater) or alongside the stent and into the intrahepatic biliary tree. Then, a retrieval balloon catheter can be inserted into the stent or above it; using standard techniques of balloon stone extraction, the stent can usually be pulled below the papilla and then removed with a snare [56]. Rarely, lithotriptor baskets, polypectomy snares, and even cholangioscopy may be required if neither a forceps or retrieval balloon is effective.…”
Section: Stent Migrationmentioning
confidence: 99%
See 1 more Smart Citation